THE FACTORS THAT MOTIVATE BALINESE WOMEN WORKING ON CRUISE SHIPS - I Made Darma Oka; Ida Ayu Ketut Sumawidari (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
The aim of this article is to understand the economic, social, and cultural factors that motivate Balinese women to work on cruise ships. This research employed qualitative and quantitative methods. The data collection was done through distributed questionaries and deep interview to Balinese women who have worked or currently working on cruise ships. The data suggested that the three aforementioned factors (economic, social, and cultural) significantly influences Balinese women to work on the cruise ships. The statistical analysis suggested that the economic factor is more dominant in motivating Balinese women to work on cruise ships, then followed by cultural and social factors. This means that the economic factor is the main reason for the Balinese women to choose the job vacancies on the cruise ships. In the light of the above finding, this study suggests, firstly a more proactive role from the government, specifically in the form of Balinese women empowerment to work on cruise ships. The empowerment can be done through the provision of proper training and education to Balinese women, so that they can compete in fillinf the job vacancies in the cruise ships. Secondly, the study also suggests for the Balinese women to prepare themselves for cruise ship opportunities by improving and developing their knowledge and skill, so they can compete in global cruise ship career competition